Stillbirth and neonatal death rates across time: the influence of pregnancy terminations and birth defects in a Western Australian population-based cohort study - Farrant, Brad M. (BMC Pregnancy Childbirth, 2016)
BACKGROUND: The stillbirth rate in most high income countries reduced in the early part of the 20(th) century but has apparently been static over the past 2½ decades. However, there has not been any account taken of pregnancy terminations and birth defects on these trends. The current study sought to quantify these relationships using linked Western Australian administrative data for the years 1986–2010. METHODS: We analysed a retrospective, population-based cohort of Western Australia births from 1986 to 2010, with de-identified linked data from core population health datasets. RESULTS: The study revealed a significant decrease in the neonatal death rate from 1986 to 2010 (6.1 to 2.1 neonatal deaths per 1000 births; p < .01), while the overall stillbirth rate remained static. The stillbirth trend was driven by deaths in the extremely preterm period (20–27 weeks; which account for about half of all recorded stillbirths and neonatal deaths), masking significant decreases in the rate of stillbirth at very preterm (28–31 weeks), moderate to late preterm (32–36 weeks), and term (37+ weeks). For singletons, birth defects made up an increasing proportion of stillbirths and decreasing proportion of neonatal deaths over the study period—a shift that appears to have been largely driven by the increase in late pregnancy terminations (20 weeks or more gestation). After accounting for pregnancy terminations, we observed a significant downward trend in stillbirth and neonatal death rates at every gestational age. CONCLUSIONS: Changes in clinical practice related to pregnancy terminations have played a substantial role in shaping stillbirth and neonatal death rates in Western Australia over the 2½ decades to 2010. The study underscores the need to disaggregate perinatal mortality data in order to support a fuller consideration of the influence of pregnancy terminations and birth defects when assessing change over time in the rates of stillbirth and neonatal death.